Teacher training and identity: a state of the art of anped wg 08 (2017-2021) (Revista Brasileira de Iniciação Científica, 2023)
It analyzes how the researchers of the Working Group (GT) 08 of the ANPEd approach teacher training and identity in the Annals of the last three editions. This is a qualitative, exploratory, State of Knowledge and content analysis research. The results indicate that the teaching identity is cultivated through initial and continuing education, through experiences and the re-signification of their practices, however, educational policies imprison the teacher, making him a producer of mechanistic teaching practices. Thus, the teaching identity is made up of training contents that disregard the teacher's trajectory in teaching.
Keywords: Continuing training; Teacher training; Training itineraries; Professional identity; Teaching work